2015
DOI: 10.1371/journal.ppat.1004757
|View full text |Cite
|
Sign up to set email alerts
|

RSV Vaccine-Enhanced Disease Is Orchestrated by the Combined Actions of Distinct CD4 T Cell Subsets

Abstract: There is no currently licensed vaccine for respiratory syncytial virus (RSV) despite being the leading cause of lower respiratory tract infections in children. Children previously immunized with a formalin-inactivated RSV (FI-RSV) vaccine exhibited enhanced respiratory disease following natural RSV infection. Subsequent studies in animal models have implicated roles for CD4 T cells, eosinophils and non-neutralizing antibodies in mediating enhanced respiratory disease. However, the underlying immunological mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 56 publications
9
138
0
1
Order By: Relevance
“…However, a study in which vaccine virus was produced in serum-free medium in different cells from that used for challenge virus, showed that FI-hRSV primed both Th1 and Th2 responses. Th2 responses mediated enhanced pulmonary pathology, pulmonary eosinophilia, mucus hypersecretion and AHR, whereas TNF-α contributed to airway obstruction and weight loss; eosinophils did not contribute to any disease parameters associated with FI-hRSV vaccine-enhanced disease in mice [89].…”
Section: Animal Models Of Rsvmentioning
confidence: 85%
See 1 more Smart Citation
“…However, a study in which vaccine virus was produced in serum-free medium in different cells from that used for challenge virus, showed that FI-hRSV primed both Th1 and Th2 responses. Th2 responses mediated enhanced pulmonary pathology, pulmonary eosinophilia, mucus hypersecretion and AHR, whereas TNF-α contributed to airway obstruction and weight loss; eosinophils did not contribute to any disease parameters associated with FI-hRSV vaccine-enhanced disease in mice [89].…”
Section: Animal Models Of Rsvmentioning
confidence: 85%
“…FI-hRSV vaccine-enhanced disease in mice is associated with priming of a Th2 response and is characterised by pulmonary eosinophilia, increased pulmonary pathology, mucus hypersecretion, weight loss, increased airway obstruction and AHR, and a reduction in lung viral load [88], [89]. Depletion of CD4 + cells or IL-4 and IL-10 abrogates vaccine-enhanced pathology [90], [91].…”
Section: Animal Models Of Rsvmentioning
confidence: 99%
“…Of course, enhanced RSV disease can be observed in the absence of eosinophil infiltration. A recent study demonstrated the same level of RSV disease in eosinophil-deficient mice although there were high levels of IL-5 expression (154). The level of RSV disease was more dependent upon the activation of Th2 subsets than on infiltration by eosinophils.…”
Section: Eosinophilic Infiltration Of Airways During Rsv Diseasementioning
confidence: 91%
“…In the 1960s, a formalin-inactivated RSV (FI-RSV) as a vaccine candidate was tested in clinical trials. However, FI-RSV trial resulted in the death of two toddlers, and most of the volunteers were hospitalized due to vaccine-enhanced disease after subsequent natural RSV infection [710]. Despite prolonged efforts to develop vaccines, there is no licensed vaccine to prevent RSV infection yet.…”
Section: Introductionmentioning
confidence: 99%